PERAN DIGITALISASI TERHADAP KEMAJUAN MASYARAKAT DESA - Rachmad Bambang (Journal of Career Development, 2023)
University of Management Lecturer Syekh Yusuf Al Makssari Gowa held a Community Service (PKM) activity in Takalar Regency on Saturday, 03 June 2023. The implementation of community service with the theme The Role of Digitalization in the Advancement of Village Communities in North Galesong District. Maccini Sombala Village, Takalar District. The results of the implementation of the activity showed the enthusiasm of the community to take part in this socialization, marked by the activeness of the participants who provided responses and questions in the discussion session. The service lecturers hope that this PKM activity can benefit the Takalar Community,